Czy emigracja z ojczyzny znaczy emigrację z języka? - Ożóg, Kazimierz (Słowo. Studia językoznawcze, 2010)
The article aims at answering the question concerning the survival of the Polish language among the emigrants staying in the foreign language and culture environment. There is a tendency for gradual disappearance of the Polish language and its vanishing from the use in the third generation of emigrants. Identification with the Polish culture spreads from the language to other spheres.